Factors affecting information communication technology acceptance and usage of public organizations in Saudi Arabia - Basri, Wael Shahhat M. (Kulliyyah of Economic and Management Sciences, International Islamic University Malaysia, 2012)
Recent developments in information communication technology (ICT) have heightened the need of more study in this topic. There is a real risk of the acceptance of ICT by some and not others contributing to the rejection. The study approaches the technology acceptance from the perspective of administration by examining the use of ICT and e-services in the public environment. The theoretical framework variables of the technology acceptance model (TAM) are examined. The study also investigated the effect of the model of organization readiness to change (MORC) Individual Differences "recipients' beliefs" as external variables, in addition subjective norm, and volunteer motivation as the moderating. The study tested the current usage as mediating variable between ICT believes and attitude to change. Most studies in ICT have been carried out in private sectors in Saudi Arabia. The survey instrument uses to collect the data is a self administrated questioner developed based on the technology acceptance questioner as used by Davis and Venkatesh in (1989). The research population is Saudi workers in public organization. The research tool is structure equation modelling (SEM), which required a minimum sample of 200 respondents. The study contributes to knowledge in the field of technology acceptance research. Mean while Technology Acceptance Model (TAM) found to be applicable in the Saudi public environment, the study found that leadership support and lack of training are the factors obstacles of the e-govemment uses. When introduced as mediators, the results verify that current usage has no effect on technology believes. Finally the findings provide invaluable implication to theory and practice. Key words: Technology Acceptance model; Information Communication Technology; ICT Usage, Public organization; structural equation modelling; Saudi Arabia and developing countries